Meeting the challenge: prevention of pneumococcal disease with conjugate vaccines - Echániz-Avilés Irma Gabriela; Solórzano-Santos Fortino (Instituto Nacional de Salud Pública, 2001)
Streptococcus pneumoniae is one of the leading causes of both invasive and noninvasive diseases in the pediatric population and continues to represent a significant public health burden worldwide. The increasing incidence of antibioticresistant strains of the pathogen has complicated treatment and management of the various pneumococcal disease manifestations. Thus, the best management strategy may be the prevention of pneumococcal diseases through vaccination. Although several pneumococcal conjugate vaccines have been clinically studied in infants and children, only a 7-valent conjugate vaccine (PNCRM7; Prevnar®/Prevenar®) is currently approved for the prevention of invasive disease. Vaccination with PNCRM7 is safe and effective in infants and young children. Routine vaccination with the conjugate vaccine could improve outcomes by safeguarding against the development of antibiotic-resistant strains of S. pneumoniae, thus simplifying the management of pneumococcal disease. Additionally, the overall costs associated with the treatment of pneumococcal diseases could be substantially reduced, particularly in developing countries. The time has come for fully applying this new advancement against S. pneumoniae, to benefit the children of the world. The Spanish version of this paper is available at: http://www.insp.mx/salud/index.html